Speed Estimation of Broadband Access to Internet via xDSL Technology - Педяш, Володимир Віталійович; Pediash, Volodymyr V.; Pedyash, Volodymyr V.; Balashov, V. A.; Oreshkov, V. I.; Barba, I. B. (My University, 2022)
The paper proposes a method for estimating the speed of broadband Internet access using information transmission systems (ITS) via xDSL technology and utilizing the vectoring system of crosstalk compensation between ITS when operating via access networks. The estimation accounts for additive interference, uncompensated crosstalk between interdependent ITS caused by using the vectoring system. The attainable access speed using the G.fast protocol was estimated depending on specifications of transmission lines, the number of ITS in operation, and the use of vectoring system.
Speed Estimation of Broadband Access to Internet via xDSL / V. A. Balashov, V. I. Oreshkov, I. B. Barba, V. V. Pedyash // Technology Radioelectronics and Communications Systems. – 2022. – Vol. 65, No. 8. – p. 439–445. DOI: 10.3103/S0735272722080052
Keywords: Research Subject Categories::TECHNOLOGY